Science fiction authors' perspectives on human genetic engineering. Issue 3 (23rd April 2021) - So, Derek; Crocker, Kelsey; Sladek, Robert; Joly, Yann
Abstract : Participants in the human gene editing debate often consider examples from science fiction but have rarely engaged directly with the science fiction community as stakeholders. To understand how science fiction authors develop and spread their views on gene editing, we created an online questionnaire that was answered by 78 authors, including 71 who had previously written about genetic engineering. When asked which ethical issues science fiction should explore, respondents most frequently mentioned affordability, new social divisions, consent and unforeseen safety risks. They rarely advocated exploring psychological effects or religious objections. When asked which works of fiction had influenced their perceptions of gene editing, the most frequent responses were the film Gattaca, the Star Trek franchise and the novels The Island of Doctor Moreau and Brave New World . Unlike other stakeholders, they rarely cited Frankenstein as an influence. This article examines several differences between bioethicists, the general public and science fiction authors, and discusses how this community's involvement might benefit proponents and opponents of gene editing. It also provides an overview of works mentioned by our respondents that might serve as useful references in the debate.